Development and Applications of Recombinant Activated Factor VII - Intasai, Nutjeera (Journal of Associated Medical Sciences, 2017)
Recombinant activated factor VII (rFVIIa) was initially developed for treatment and prevention of bleeding during surgery and invasive procedures in congenital hemophilia with inhibitors against coagulation factors. Extensive research over the last few decades has contributed to the development of rFVIIa. These thorough studies not only helped to improve the biological activity and half-life of rFVIIa but also to enhance the knowledge regarding the mechanisms of action of rFVIIa to re-establish normal hemostasis. Since rFVIIa has been successfully in use for hemophilia treatment, it has been extended to other coagulopathies which characterized by the impairment of thrombin generation, including acquired hemophilia, Glanzmann’s thrombasthenia, and congenital FVII deficiency. The development, the mechanism of action, and the clinical applications of rFVIIa are reviewed in this article.